Case study on power generation from waste on the Sinhgad Technical Education Society (STES) Campus, Lonavala, Maharashtra - Shenbaga lakshmi; Sagar Babar jadhav (Kuwait Journal of Science)
The present study examines the viability of harnessing solid waste and food waste for power generation inside the STES campus, Lonavala, Maharashtra, India. An extensive study has been carried out to evaluate the performance of biomass gasification technology which provides a key point to reduce CO2 emission associated with electricity generation. The biomass energy is yet to be developed due to the major barriers like lack of complete knowledge about the biomass resources, economic barriers associated with transportation and storage of resources. This study completely elucidates the various methods of harnessing energy from Biomass resources their merits and demerits.